Revitalization of urban waterfornt : The design process and Design Elements - Ahmed Abdelrahman Saad Ghazy; Hussein Samir Salama (Cairo : Ahmed Abdelrahman Saad Ghazy, 2017)
Through history waterfornt redevelopment have experienced several phases of development strategies and become the most challenging topic for urban designers and planners in the world now
Thesis (M.Sc.) - German University - Faculty of Postgraduate Studies and Scientific Research - Department of Architecture Urban Design